Utilization of Red Fruit on The Growth of Tissue Granulation in Diabetic Wounds - Santalia Banne Tondok; Demianus Tafor; Sethiana Dewi Ruben; Wanuliana Wanuliana; Nasrah Nasrah (Postgraduate, University of Mataram, 2023)
The utilization of red fruit on the growth of granulation tissue in diabetic wounds aims to determine the benefits of red fruit which have been scientifically proven through research in Indonesia. Methods: Conducting a literature search using the Google Scholar application and conducting an analysis of the literature included in the inclusion criteria. Results: From the search results and research results which conclude about the benefits of red fruit. Conclusion: The benefits of red fruit on the growth of granulation tissue in diabetic wounds, namely red fruit contains carotene (12,000 ppm), beta-carotene (700 ppm), tocopherol (11,000 ppm). The benefits of red fruit on the growth of granulation tissue also affect diabetic wound healing because granulation tissue is the growth of new tissue that occurs when a wound is undergoing a healing process, consisting of new capillaries and fibroblast cells that fill the cavity. Granulation tissue formation is an important step in the proliferative and healing phase of the wound. Granular tissue is a reddish network that contains capillaries at the base of the wound